The Use Of Digital Media In Fiqh Instruction In Elementary Madrasah In The Digital Age - Kirana (Journal Innovative Practices in Education (JIPE), 2026)
Teaching variation skills are essential for creating engaging learning environments, and the development of digital technology has had a significant impact on the field of education, including Fiqh learning in Madrasah Ibtidaiyah (Islamic Primary Schools). The use of digital media, such as instructional videos, interactive presentations, educational applications and online learning platforms, can help improve the effectiveness of the learning process. This study aims to describe the use of digital media in Fiqh learning for Year 5 pupils in the digital age. The research method employed is a literature review based on the analysis of various relevant academic sources. The findings indicate that digital media can enhance pupils’ motivation to learn, facilitate their understanding of learning materials, increase pupil participation, and support independent learning. However, several challenges remain, including limited technological facilities, teachers’ digital competencies, and the supervision of pupils’ use of digital devices. Therefore, collaboration between schools, teachers, and parents is necessary to optimise the use of digital media in Fiqh learning.